The Arab revolts : dispatches on militant democracy in the Middle East - McMurray, David A.; Ufheil-Somers, Amanda (Public cultures of the Middle East and North Africa., 2013)
The 2011 eruptions of popular discontent across the Arab world, popularly dubbed the Arab Spring, were local manifestations of a regional mass movement for democracy, freedom, and human dignity. Authoritarian regimes were either overthrown or put on notice that the old ways of oppressing their subjects would no longer be tolerated. These essays from Middle East Report - the leading source of timely reporting and insightful analysis of the region - cover events in Tunisia, Egypt, Bahrain, Syria, and Yemen. Written for a broad audience of students, policymakers, media analysts, and general readers, the collection reveals the underlying causes of the revolts by identifying key trends during the two decades leading up to the insurrections.